(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective: To determine the impact of gestational diabetes on maternal and fetal characteristics during pregnancy Study design: A retrospective comparative study Place and Duration: This study was done in Sobhraj Maternity Hospital Karachi from November 2021 to November 2022 Methodology: A total of 120 pregnant women were examined for this investigation, separating 90 into the study group with gestational diabetes and 30 into the control group without diabetes. The risk factors and complications in the two study groups were analysed using statistical software, and the results were presented in the form of tables. Results: Results showed that the need for caesarean delivery was higher in the GDM group, with fetal distress being a significantly indicating for this type of delivery. Gestational hypertension was also more common in the GDM group, which was found to increase the risk of premature birth. The occurrence of neonatal respiratory distress was particularly higher inmothers of newborns with GDM, and premature birth was more common in the GDM group. Diet-based treatment was the most common method of blood sugar control in the GDM group. The occurrence of iron deficiency anemia was significantly higher in expectingmothers with GDM compared to the control group. Conclusion: The results of our study suggest that gestational diabetes is associated with an increased need for caesarean delivery, as well as an increased risk of gestational hypertension, fetal distress, preterm birth, neonatal respiratory distress, and iron deficiency anemia.